2013
DOI: 10.12968/live.2013.18.5.166
|View full text |Cite
|
Sign up to set email alerts
|

Veterinary vaccination advice and perceived farmer compliance on UK dairy farms

Abstract: Vaccination is a commonly used disease control strategy in dairy farming in the UK. Farmers perceive their veterinarian to be the most important source of information for vaccination advice. However, poor compliance and perceived confusion on appropriate vaccination strategies suggest that there is variation in the advice that farmers are receiving. This study compared veterinarians', veterinary students' and farmers' perceptions and approach to vaccination strategies on dairy farms through the use of survey q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
1
12
1
Order By: Relevance
“…It therefore follows that decision-making around vaccination and disease control on farms should be emphasised in the undergraduate veterinary curriculum. Cresswell and others (2013) showed that there was a difference in vaccination advice given by vets in practice versus final year students. This difference could be attributed to a lack of knowledge of cattle vaccination and the absence of clinical experience to determine the advice and information relevant to a particular farm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It therefore follows that decision-making around vaccination and disease control on farms should be emphasised in the undergraduate veterinary curriculum. Cresswell and others (2013) showed that there was a difference in vaccination advice given by vets in practice versus final year students. This difference could be attributed to a lack of knowledge of cattle vaccination and the absence of clinical experience to determine the advice and information relevant to a particular farm.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research can offer a useful insight into the question of vets’ vaccine‐related decision‐making. For example, in a discussion group study of vets’ opinions on dairy cattle vaccination, Cresswell and others (2013) highlighted a concern regarding variation in vaccination advice from vets. The authors suggested that this was partly the result of a lack of evidence‐based information, making it difficult to present a common approach to veterinary vaccination advice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“… Cresswell and others (2014) as well as Meadows (2010) found evidence of poor vaccination compliance by cattle farmers to cold chain storage and administration recommendations. Dairy practitioners’ main concerns with regard to cattle vaccination also included issues of compliance ( Cresswell and others 2013 ).…”
mentioning
confidence: 99%
“…Vets’ perception of their role and communication style can be at odds with farmers’ reported preferences (Hall and Wapenaar 2012). These inconsistencies as well as differences in ‘veterinarian perceived’ and ‘farmer reported’ barriers to vaccination (Cresswell and others 2013) could result in miscommunication or a lack of discussion surrounding vaccination strategies. With an improved understanding of farmers’ perceptions of the vets’ role, more tailored advice could be provided by vets.…”
mentioning
confidence: 99%